Understanding the use of sex pilus specific bacteriophages to reduce conjugative dissemination of antibiotic resistance - Maluping, Ramon (2023)
Antimicrobial resistance (AMR) is considered as one of the greatest threats to human public health and in agriculture and food security. To address this threat, a Global Action Plan encourages development of alternatives to antibiotics, including the use of bacteriophage to control infections. A large proportion of transmissible antibiotic resistance is encoded on conjugative plasmids. Transmission requires sex pili and a sex pilus targeting (SPS) phage could provide a selection against plasmid carriage.